Biphasic pretreatment for energy and carbon efficient conversion of lignocellulose into bioenergy and reactive lignin. (1st December 2021) - Islam, Md Khairul; Rehman, Shazia; Guan, Jianyu; Lau, Chun-Yin; Tse, Ho-Yin; Yeung, Chi Shun; Leu, Shao-Yuan
Graphical abstract: Highlights: A novel biphasic pretreatment was investigated for Acacia Confusa wood biorefinery. Pretreated substrate resulted 92.2% digestibility and 0.41 g/g-glucan ethanol yield. Preserved 42.5% of original β-O-4 linkages in fractionated lignin. More than 50% of wood carbon was recovered as ethanol and reactive lignin. Reduced 32.4% of energy consumption to yield net positive energy of 1.1 MJ/kg-wood. Abstract: Lignocellulosic biomass is an emerging resource of carbohydrates and bio-based aromatics derived from biorefinery. However, pretreatment of biomass to fractionate building-block chemicals is an energy-intensive process affecting the sustainability of the whole process. This study aims to investigate the energy and carbon benefits of a novel biphasic pentanol-water pretreatment. To compare, three different pretreatment scenarios i.e., dilute acid, conventional ethanosolv, and biphasic pentanol-water pretreatments were investigated for the conversion of Acacia Confusa wood chips to produce benchmark fuel and reactive lignin. The results showed that the proposed biphasic pretreatment yielded 70.3% lignin dissolution in the organic phase while leaving cellulose as an insoluble solid residue. Simultaneous saccharification and fermentation resulted in 92.2% cellulose digestibility of pretreated substrates and ethanol yield of 0.41 g/g-glucan in the fermentation broths. Biphasic pretreatment also preserved 42.5% of reactive β-aryl ether linkages in fractionated lignin which is higher than ethanosolv pretreatment (31.1%). Carbon balance showed that the biphasic process recovered 50.3% wood carbon in the product streams as ethanol and reactive lignin, which is higher than the dilute acid (17.1%) and ethanosolv (49.6%) approaches. The overall energy balance showed that the biphasic process yielded net positive energy of 1.1 MJ/kg-wood which was much higher than the dilute acid (−0.16 MJ/kg) and ethanosolv (−1.6 MJ/kg) processes. This was due to the physical separation of dissolved sugars and lignin which reduced about 32.4% of the total energy consumption compared to ethanosolv biorefinery indicating the feasibility of the proposed biphasic process.